Cardiovascular Autonomic Neuropathy as a New Complication of Postsurgical Chronic Hypoparathyroidism. (14th December 2018) - Tabacco, Gaia; Naciu, Anda Mihaela; Maggi, Daria; Santonati, Assunta; Pedone, Claudio; Cesareo, Roberto; Bosco, Daniela; Gaspa, Gianluigi; Napoli, Nicola; Pozzilli, Paolo; Manfrini, Silvia; Palermo, Andrea
ABSTRACT: Postsurgical hypoparathyroidism (hypoPT) increases fatigue and seems to affect the risk of mortality. Cardiovascular autonomic neuropathy (CAN) is an impairment of the cardiovascular autonomic system, a cause of increased mortality, and associated with increased fatigability. The aim of this study is to evaluate CAN in hypoPT and its relationship with hypocalcemia, PTH levels, and hyperphosphatemia. This is a cross‐sectional study comparing 51 postsurgical hypoPT patients treated with calcium and calcitriol and 43 control subjects without any PTH/calcium/phosphate disorders who underwent thyroidectomy. CAN was assessed by heart rate (HR) response to deep breathing, HR response to the lying‐to‐standing test, HR response to the Valsalva maneuver, and blood pressure response to standing. Participants were considered to have "early CAN" if they had one abnormal result in the HR tests and "definite CAN" with two or more abnormal results. The prevalence of CAN was 23% in the control group and 78% in the hypoPT group (OR 11.48; 95% CI, 4.48 to 32.17). Patients with hypoPT and serum calcium (sCa) ≥8.5 mg/dL had a prevalence of early CAN of 72.4% and the prevalence was 86.4% in those with sCa <8.5 mg/dL. Definite CAN was found in 2.3% of the control group, 24.1% of the hypoPT group without hypocalcemia, and 59.1% of the hypoPT group with hypocalcemia. In the hypoPT group, the OR for definite CAN in the patients with hypocalcemia compared to the patients with normocalcemia was 4.54 (95% CI, 1.36 to 15.11). The association between low sCa and definite CAN was confirmed after adjustment for confounders with OR 13.62 (95% CI, 2.12 to 149.84). No association was found between definite CAN and PTH levels or high phosphate levels. HypoPT is associated with CAN and hypocalcemia seems to affect its severity. Larger and prospective studies are needed to confirm our findings. © 2018 American Society for Bone and Mineral Research.